Association between arterial stiffness and left ventricular diastolic function: A large population-based cross-sectional study - Kim, Minkwan; Kim, Hack-Lyoung; Lim, Woo-Hyun; Seo, Jae-Bin; Kim, Sang-Hyun; Kim, Myung-A; Zo, Joo-Hee (Frontiers in Cardiovascular Medicine, 2022)
Background The association between arterial stiffness and left ventricular (LV) diastolic function has been demonstrated in several studies, but the samples size in those studies was small. This study aims to verify this issue in a large number of study subjects. Methods A total of 7,013 consecutive participants (mean age 60.6 years and 43.3% female) who underwent both baPWV and transthoracic echocardiography were retrospectively analyzed. Subjects with significant cardiac structural abnormalities were excluded. Results There were significant correlations of baPWV with septal e′ velocity (r = − 0.408; P < 0.001), septal E/e′ (r = 0.349; P < 0.001), left atrial volume index (LAVI) (r = 0.122; P < 0.001) and maximal velocity of tricuspid valve regurgitation (TR Vmax) (r = 0.322; P < 0.001). The baPWV values increased proportionally with an increase in the number of LV diastolic indices meeting LV diastolic dysfunction criteria (P-for-trend < 0.001). In multivariable analyses with adjustment for confounding effects of various clinical covariates, higher baPWV was independently associated with septal e′ < 7 (odds ratio [OR], 1.30; 95% confidence interval [CI] 1.20–1.60; P < 0.001), septal E/e′ ≥ 15 (OR, 1.46; 95% CI, 1.21–1.78; P < 0.001), and TR Vmax > 2.8 m/s (OR, 1.60; 95% CI, 1.23–2.09; P < 0.001) but not with LAVI ≥ 34 mL/m2 (OR, 0.89; 95% CI, 0.76–1.03; P = 0.123). Conclusions Increased arterial stiffness, as measured by baPWV, was associated with abnormal diastolic function parameters in a large number of study participants, providing strong evidence to the existing data about ventricular-vascular coupling.